2020
DOI: 10.3389/fphys.2020.00647
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Size and Function in Sherpa Living High, Sherpa Living Low and Nepalese Lowlanders

Abstract: High-altitude (HA) natives have evolved some beneficial responses leading to superior work capacity at HA compared to native lowlanders. Our aim was to study two responses potentially protective against hypoxia: the spleen contraction elevating hemoglobin concentration (Hb) and the cardiovascular diving response in Sherpa highlanders, compared to lowlanders. Male participants were recruited from three groups: (1) 21 Sherpa living at HA (SH); (2) seven Sherpa living at low altitude (SL); and (3) ten native Nepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 49 publications
(103 reference statements)
11
29
0
Order By: Relevance
“…The difference between the results in these two similar studies could possibly be caused by a general catabolism in the "Death Zone" above 8000 m, not allowing spleen enlargement. It was also recently observed that top climbers had larger spleens and spleen contraction during apnea, compared to recreational high altitude trekkers (Schagatay et al 2020). Taken together these studies suggest that also the spleen itself may be subject to altitude acclimatization, which is in line with the current study's observations of a significant spleen function in elevating Hb at altitude.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The difference between the results in these two similar studies could possibly be caused by a general catabolism in the "Death Zone" above 8000 m, not allowing spleen enlargement. It was also recently observed that top climbers had larger spleens and spleen contraction during apnea, compared to recreational high altitude trekkers (Schagatay et al 2020). Taken together these studies suggest that also the spleen itself may be subject to altitude acclimatization, which is in line with the current study's observations of a significant spleen function in elevating Hb at altitude.…”
Section: Discussionsupporting
confidence: 91%
“…However, in that study, the spleen contraction during apnea at 1370 m was not significantly associated with AMS symptoms (P = 0.121; Holmström et al 2019). It was however recently found that spleen baseline volume was greater in experienced mountaineers going to climb Mt Everest, than in Mt Everest Base Camp trekkers (Schagatay et al 2020), suggesting that spleen function is important for successful climbing at high altitude. It was also recently reported that larger spleens and more powerful contractions were present in the Sherpa population of high altitude origin, compared to Nepali lowlanders (Holmström et al 2020).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations